A20 Inhibits Intraocular Inflammation in Mice by Regulating the Function of CD4+T Cells and RPE Cells - Hu, Jianping; Yi, Shenglan; Wang, Chaokui; Zhang, Yiting; Tang, Jihong; Huang, Xinyue; Yang, Lu; Yang, Jinglu; Li, Hong (Frontiers in Immunology, 2021)
A20 is a negative regulator of inflammation and immunity and plays a role in several autoimmune and inflammatory diseases. Here, we demonstrate that A20 overexpression significantly ameliorates severity of EAU by inhibiting the infiltration of Th1 and Th17 cells, and by protecting integrity of the blood retinal barrier. In vitro studies showed that A20 could promote CD4+T cells towards a Th1 and Th17 phenotype. A decreased expression of A20 in CD4+T cells was noticed in active BD patients but not in VKH patients. Furthermore, silencing of A20 in hRPE cells induced the production of IL-6, IL-8 and MCP-1 and downregulated ZO-1 and occludin expression which is mediated by inhibition of MAPK and NF-κB pathways. This study reveals a mechanism by which A20 prevents autoimmune uveitis.